Current status of management of stress hyperglycemia in stroke patients with enteral nutrition (脑卒中肠内营养应激性高血糖的管理现状) - GAO Ya (高雅); LIU Guiying (刘桂英) (中西医结合护理, 2023)
Patients after stroke are often accompanied by disorders of consciousness and swallowing disorders, and giving enteral nutrition is of great significance to avoid malnutrition and improve the prognosis. Stress hyperglycemia is a common complication in the acute phase and has an unfavorable prognosis. Enteral nutrition has an impact on blood glucose. In this paper, a literature search on related issues was conducted, in order to review the relationship between enteral nutrition and blood glucose, intestinal nutrition, hyperglycemia, and Traditional Chinese Medicine care technology-assisted hypoglycemic treatment. (脑卒中患者常伴有意识障碍、吞咽障碍, 给予肠内营养对避免营养不良、改善预后具有重要意义。应激性高血糖是急性期常见并发症, 对患者预后不利。肠内营养会对血糖产生影响, 本文就相关问题进行文献检索, 对肠内营养与血糖的关系、肠内营养的管理、高血糖的管理以及中医护理技术辅助降糖进行综述。)